МАГНІТНЕ ПОЛЕ НАДВИСОКОВОЛЬТНОЇ ДВОЛАНЦЮГОВОЇ КАБЕЛЬНОЇ ЛІНІЇ З ІЗОЛЯЦІЄЮ ЗІ ЗШИТОГО ПОЛІЕТИЛЕНУ - Кучерява, І.М. (Інститут електродинаміки Національної академії наук України, 2019)
The magnetic field generated by underground two-circuit 330 kV cable line with XLPE insulation is studied. The skin effect and proximity effect in the power cables are analyzed. The distributions of magnetic field on the ground for different distance between the cable circuits are computed and discussed. As shown for the case under consideration, the external magnetic field of cable power line can be reduced down to admissible safety level by using another ways. References 8, figures 6.